Characterisation of Ground Coal Bottom Ash With Different Grinding Times - Mohd Khairy, Burhanudin; Mohd Haziman, Wan Ibrahim; Putra Jaya, Ramadhansyah; B. Sri, Umniati (UTHM, 2023)
The physical and chemical composition of Ground Coal Bottom Ash (GCBA) exposed to varying grinding periods is discussed in this article. CBA was pulverised for 20 hours, 30 hours, and 40 hours in a ball mill machine. Particle Size Analyzer (PSA) and X-ray Fluorescence (XRF) instrument were used to characterise GCBA. According to the results of the tests, GCBA with a grinding duration of 40 hours generates the largest percentage of the finest particle (50-1000 nm) at 4%, the specific surface area is 13528.18 cm2/cm3, and the specific gravity (SG) is 2.54. According to the XRF results, there are no significant variations in the chemical compositions of the CBA with varying grinding periods. At 20, 30, and 40 hours grinding time, the primary oxide element for SiO2 is 51.5%, 53.8%, and 52.3%, while Al2O3 is 14.3%, 15.1%, and 14.6%, and Fe2O3 is 5.08%, 5.27%, and 5.07% respectively. The sum of three primary oxide constituents surpasses the 70% ASTM C618 limit for pozzolanic material Class F fly ash. © Universiti Tun Hussein Onn Malaysia Publisher’s Office.